한국의 한국계중국인 대상 정책의 전개: `동포`와 `외국인력` 사이의 절충 - 최서리; Seori Choi; 이창원; Chang Won Lee; 박미화; Mihwa Park (다문화와 평화, 2016)
흔히 `조선족`으로 불리는 한국계중국인은 한국사회에서 가장 큰 이주민 집단을 형성하고 있다. 뿐만 아니라 장기 거주하는 규모도 빠르게 증가하여 이들은 이미 한국사회의 비중 있는 구성원이 되었다. 일부 학자들은 한국계중국인의 귀환 촉진 및 체류 우대정책을 민족주의의 발로로 해석하고 있지만, 이 정책은 내적으로 상당히 모순적이다. 이 연구는 정부의 한국계중국인에 대한정책을 시기별로 살펴보면서 정책의 논거를 분석한다. 지난 20여 년간 한국계중국인 대상 정책은 한편으로는 한민족 `동포`를 수용해야 한다는 명분이, 다른 한편으로는 국내 취약계층의 일자리를 보호해야 한다는 명분이 경합하는 장(field)이 되었다. 동포 우대와 국민 권리 보호라는 두 가지 가치가 경합하는 가운데 상황에 따라 근시안적 관점에서 추진된 정책은 한국계중국인을 `한국사회에서 배제된 정주자`로 애매하게 위치시키는 결과를 낳았다. 한국계중국인의 거주가 장기화되는 상황에서 이제는 한국 정부가 이들을 동등한 사회구성원으로 인식할 필요가 있다. 특히 한국계중국인의 노동시장 상향이동 가능성이 없다면 이들의 주변화가 심화될 것이며, 이들은 결국 우리 안의 타자로 남게 될 것이다. Chinese people of Korean ethnicity, commonly known as Joseonjok, have emerged as the largest migrant group in Korea. As an increasing number of these Korean-Chinese have settled in Korea, they have become a visible group within Korean society. Some scholars claim that the return policy of Korean-Chinese is a reflection of nationalism in Korea, but the government policy towards Korean-Chinese has been quite contradictory. This paper offers a critical review of government policy with regards to Korean-Chinese and an analysis of the rationale behind such policy. The policy towards Korean-Chinese over the past twenty years has been a field in which two policy values and goals compete. On the one hand, the government has been urged to embrace Korean diaspora. On the other hand, the government has been obliged to protect the right of disadvantaged citizens to secure local jobs. While the two policy goals (ethnic priority and the protection of the citizen`s right to work) have been competing, Korean-Chinese have continued to be the subject of control. The past policy of Korean-Chinese has thus contributed to the production of the socially excluded in Korea. As the permanent settlement of Korean-Chinese tends to become the norm, the Korean government needs to accept them as equal member of Korean society. Without the possibility of upward mobility in the labor market, Korean-Chinese will continue to be marginalized and remain racialized `Others` within society.